2013
DOI: 10.2320/matertrans.m2012333
|View full text |Cite
|
Sign up to set email alerts
|

The Structure of an Al&ndash;Co&ndash;Ni Decagonal Quasicrystal in an Al<sub>72</sub>Co<sub>8</sub>Ni<sub>20</sub> Alloy Studied by Cs-Corrected Scanning Transmission Electron Microscopy

Abstract: The structure of an AlCoNi decagonal quasicrystal in an Al 72 Co 8 Ni 20 alloy has been examined by Cs-corrected high-angle annular detector dark-field (HAADF)-and annular bright-field (ABF)-scanning transmission electron microscopy (STEM) observations with the incident beam parallel to the periodic axis. Observed ABF-and HAADF-STEM images clearly show the existence of large columnar clusters of a decagonal section with an about 3.2 nm in diameter and their arrangement with bond-orientational order (BOO) of a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 14 publications
1
22
1
Order By: Relevance
“…2a. From the previous interpretations [1,3,5], it can be concluded that all bright dots connected by lines in Fig. 2a and in Fig.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…2a. From the previous interpretations [1,3,5], it can be concluded that all bright dots connected by lines in Fig. 2a and in Fig.…”
Section: Methodsmentioning
confidence: 99%
“…3a, with an edge-length of 0.25 nm, and consequently the TM atoms and MSs are arranged with BOO. The pentagonal arrangements of MSs in pentagonal frames with denite directions can be seen in the B plane of the structure of W(AlCoNi) [1,10] and τ 2 -Al 3 Co [2] crystalline phases, which are considered to be important approximants for the interpretation of Al-TM decagonal quasicrystals and in quasiperiodic planes of several types of Al-Co-Ni decagonal quasicrystals [1,4,5]. is generated by the projection of a ve-dimensional (5D) hyper-cubic lattice through a window of Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Introduction Six types of decagonal quasicrystals (DQCs) and some crystalline approximants have been found in Al-Co-Ni alloys with various compositions from 8 to 25.5 at % Co and from 20 to 5 at % Ni, respectively, with a nearly constant Al content from 70 to 72 at % [1][2][3][4][5], and so the stability of these DQCs formed in alloys with different Ni/Co ratios is considered to be affected by chemical ordering of Co and Ni. However, the study of the chemical ordering of Co and Ni in the Al-Co-Ni DQCs and their approximants has never been performed, because it has been difficult, if not impossible, to distinguish between neighbouring elements Co and Ni, which show very similar contrast to both electron and X-ray probes, although transition-metal (TM) atom arrangements have been exactly determined by recent Cs-corrected scanning transmission electron microscopy (STEM) observations [6][7][8][9][10][11].…”
Section: Please Scroll Down For Articlementioning
confidence: 98%
“…It should be noticed that two types of the 1.2 nm clusters with opposite orientations of the pentagonal arrangements at their centres are arranged in an ordered manner in such a way that two clusters connected by a bond are always different. Figure 2b is derived from the arrangement of bright dots in Figure 2a on the basis of structures of the W-(AlCoNi) phase [6] and several Al-TM DQCs and crystalline approximants [6,7,[9][10][11]. The 1.2 nm clusters arranged with an interval of 2 nm are connected by two types of pentagonal tilings with a bondlength of 0.76 nm, as indicated by solid and broken lines in Figure 2a.…”
Section: Philosophical Magazine Letters 541mentioning
confidence: 98%
See 1 more Smart Citation